Nanozyme-based lateral flow assay for the sensitive detection of Escherichia coli O157:H7 in milk - Han, Jiaojiao; Zhang, Lei; Hu, Liming; Xing, Keyu; Lu, Xuefei; Huang, Youju; Zhang, Jiawei; Lai, Weihua; Chen, Tao (Journal of dairy science, 2018)
Lateral flow assay (LFA) has been applied in many fields due to its relative ease of use and cost-effectiveness. However, it has low sensitivity and its applications are limited. Probe materials play a significant role in improving the detection efficiency and sensitivity of LFA. In this study, by using concave palladium-platinum (Pd-Pt) nanoparticles as a nanozyme probe, we developed a sensitive LFA based on the sandwich format for qualitative and quantitative detection of Escherichia coli O157:H7. The sensitivity of the LFA was improved by applying the 3,3′,5,5′-tetramethylbenzidine (TMB) substrate onto the test line where the nanozyme was accumulated in the presence of analytes. The nanozyme showed high catalytic performance toward TMB and greatly enhanced the signal intensity of the test line. The sensitivity of the nanozyme-based LFA was 9.0 × 102 cfu/mL in milk, which was 111-fold higher than that of traditional colloidal gold-based LFA. The proposed method has remarkable potential in the detection of various pathogens in real samples.